Effectiveness of yellow maize testers with varying resistance reactions to Striga hermonthica for evaluating the combining ability of maize inbred lines - Zebire, D.; Menkir, A.; Adetimirin, Victor O.; Mengesha Abera, W.; Meseka, S.; Gedil, Melaku A (MDPI, 2020)
The choice of an appropriate tester is important for success in resistance hybrid breeding programs. Limited information is available on the most suitable testers that allow the selection of yellow endosperm maize inbred lines with good combining ability for resistance to witchweed (Striga hermonthica) and superior agronomic performance in hybrids targeted to areas infested with the parasite. Testcrosses of 30 Striga-resistant yellow endosperm maize inbred lines with three testers having varying levels of resistance to S. hermonthica were evaluated at Abuja and Mokwa in Nigeria under Striga-infested and non-infested conditions in 2018 and 2019. The lines × tester interaction was significant for grain yield under Striga infestation, indicating that the performance lines in testcrosses varied with the testers. The respective average general combining ability effect of lines and testers was 1.5 and 32.4 times greater than the corresponding specific combining ability effects under infestation, showing the greater importance of additive gene action controlling the performance of testcrosses under Striga infestation. The different testers exhibited a different capacity to discriminate among the test lines with the susceptible tester being the least effective. Most of the criteria used to determine the best tester favored the selection of the tolerant and resistant testers as promising candidates to identify superior Striga-resistant yellow endosperm inbred lines for the hybridization and development of resistant hybrids. The results of this study demonstrated that testers with a high frequency of desirable alleles were superior to the tester with a low frequency of favorable alleles in hybrid breeding programs for resistance to S. hermonthica.